Breakthrough infection after Covishield COVID-19 vaccine among health care workers at Patan Academy of Health Sciences, Nepal (Journal of Patan Academy of Health Sciences, 2021)
Introduction: Coronavirus Disease 2019 (COVID-19) vaccines have an important role in the control and prevention of the pandemic. However, infection after vaccination, though uncommon, has been reported after partial or complete immunization. This study aims to find out vaccine breakthrough infection after the Covishield COVID-19 vaccine.Method: This cross-sectional survey was conducted among the health care workers (HCWs) from May 2021 to July 2021 at Patan Hospital, Patan Academy of Health Sciences, Nepal who received the Covishield vaccine. The data were collected using Google form and a printed questionnaire on COVID 19 breakthrough infection ≥2w after vaccination. The rate of breakthrough infection, hospitalization, and its association with age, gender, and working departments of HCWs was analyzed using SPSS. Ethical approval was obtained.Result: Out of 1462 HCWs approached, 880 completed the survey, among which 819 (93.1%) had a completed vaccination status. Infection after the first and before the second dose was 164 (18.7% of 880) and after two doses 131 (16%). The breakthrough infection occurred in 83 (10.1% of 819). There was no statistically significant association of breakthrough infection with age, gender, and working department of HCWs. Total 74 (8.4%) were managed by admission in hospital.Conclusion: The findings of this study reveal a low breakthrough infection rate after Covishield vaccination among HCWs at Patan Academy of Health Sciences, Kathmandu, Nepal. Overall, COVID-19 infection rates decreased after the first and second dose of the vaccine.